Cannabis for medical purposes: A cross-sectional analysis of health care professionals' knowledge. Issue 1 (19th January 2022) - Rice, Jessica; Hildebrand, Andrea; Waslo, Carin S.; Cameron, Michelle H.; Jones, Kim Dupree
ABSTRACT: Background: Legalization of cannabis use and the evidence base supporting both risks and benefits of cannabinoids are expanding, but our understanding of health care professionals' (HCPs) knowledge about cannabis for medical purposes is limited. Understanding of the knowledge base and knowledge gaps about medical cannabis use is critical to advanced practice registered nurses (APRNs) because they are increasingly called on to manage patients taking multiple drugs, including prescribed and unprescribed cannabis and prescription cannabinoids. Purpose: The purpose of this study was to examine HCPs' knowledge of clinical cannabis, including laws and regulations; risks and harms; pharmacology; and effects on pain, multiple sclerosis spasticity, and seizures as assessed with written tests before an in-person, continuing medical education program. Methods: Total scores and differences among professions and topics were compared. Results: A total of 178 of the 226 program attendees completed the test (79%) (107 [47%] physicians, 30 [13%] APRNs, and 18 [8%] registered nurses). The mean test score was 63.2% (SD = 12.7%) without significant differences among professions ( F (3, 174) = 1.53; p = .21) but with significant differences among topics (χ 2 (7, 1068) = 201.13; p < .001). The score was lowest for effects on seizures (43.8%) and with scores below 70% for all other areas except laws and regulations (85.7%). Implications for practice: There are substantial gaps in HCPs' knowledge about the clinical effects of cannabis, especially about risks and harms, pharmacology, and the effects on pain, multiple sclerosis spasticity, and seizures. Further education may help HCPs to understand the risks and benefits of cannabis and cannabinoids across conditions.